Higher order Homotopy Taylor-Pertubation via startsystem - Nor Hanim, Abd Rahman, Dr. (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2014)
Link to publisher's homepage at http://amci.unimap.edu.my